The Painted Queen [compact disc, unabridged] : an Amelia Peabody novel of suspense - Peters, Elizabeth, 1927-2013; Hess, Joan (Peters, Elizabeth, 1927-2013. Amelia Peabody series., 2017)
Egypt, 1912. Amelia Peabody and her dashing archeologist husband, Radcliffe Emerson, are once again in danger as they search for a priceless, stolen bust of legendary Queen Nefertiti and Amelia finds herself the target of assassins.